Do prescrito ao realizado: as demandas interacionais das ligações para o Disque Saúde da Mulher e sua relação com as instâncias de prescrição do trabalho de atender - Souza, Joseane de (Universidade do Vale do Rio do Sinos, 2009)
This study derives from a larger research project that verifies how the interactions between the Disque Saúde call takers and women that seek the service occur. This larger project, as well as the present study, is performed through the theoretical-analytical perspective of Conversation Analysis. The data comprise 126 audio-recorded interactions during a two-week incursion at the SUS information center in Brasília, where the Disque Saúde call center is located, and data about the institution’s working context, collected throughout the period of one year. The recorded interactions were transcribed and revised according to conventions proposed by Jefferson (1984), translated and adapted by Schnack, Pisoni and Ostermann (2005). The main focus of this paper is to describe and discuss two moments in the interactions between the callers and the call takers of Disque Saúde: I) the moment of construction of the understanding of what the callers’ request might be, that is, the reason for the call – which happens via
Keywords: Disque Saúde; interação - atendentes - pacientes; interaction; Letras e Artes; Lingüística